P328 Thematic analysis of chemical emergency exercises by content analysis technique. (1st September 2016) - Kalatpour, Omid; Ajdari, Mohamad
Abstract : To manage a chemical emergency situation in an effective way it is necessary to have certain capabilities. These capabilities focus on preventing, protecting against, responding to, and recovering from the major events. Designing a system of emergency exercises without a balanced approach for all capabilities may endanger the public. The main objective of this study is finding the main concentration of the practiced exercises on the desired capabilities. The content Analysis technique was used to conduct a thematic analysis of the contents of records of some implemented scenarios. The findings showed that there was not a balanced system for enhancing the needed capabilities. Most of the planning attempts concentrated on the response phase and aspects like the protection and recovery capabilities were ignored. To plan an exhaustive system of emergency preparedness such findings are helpful.